RETRACTED ARTICLE: Two new metal coordination polymers: anticancer activity in endometrial carcinoma. Issue 4 (4th May 2018) - Duan, Liyan; Zhang, Kequn; Wang, Yanqiu; Jin, Jian; Xie, Junyan; Luo, Xiang; Deng, Qiaozi
Abstract: We, the Editors and Publisher of the journal Inorganic and Nano-Metal Chemistry, have retracted the following article: Liyan Duan, Kequn Zhang, Yanqiu Wang, Jian Jin, Junyan Xie, Xiang Luo & Qiaozi Deng Two new metal coordination polymers: anticancer activity in endometrial carcinoma, Inorganic and Nano-Metal Chemistry. 2019; VOL. 48, NO. 4-5, 257–261. DOI: 10.1080/24701556.2018.1513529 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to address the concerns raised and have not been able to provide sufficient supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.